Physiological and molecular characterization of Microbacterium paraoxydans isolated from ponds in Cuatrociénegas, Coahuila - Salinas-Jasso, Thalía Athenas; Moreno- Dávila, Ileana Mayela M.; De León-Zapata, Miguel Ángel; Soria-Ortiz, Alma Idalia (Ecosistemas y Recursos Agropecuarios, 2024)
The Cuatrociénegas valley has an important ecological reserve composed of several ponds and dunes which are rich in calcium and magnesium salts. The biocenosisbelonging to the valley presents a high level of endemism and biodiversity. This microbial diversity is of biotechnological interest due to the diverse metabolic mechanisms that these microorganisms use to adapt and grow in extreme desert conditions. The objective of thestudy was to physiologically and molecularly characterize a bacterium isolated from a pondin Cuatrociénegas, to know its enzymatic capacity and to determine its biotechnological potential. It was morphologically characterized; optimum growths for pH, temperature and salt concentrations were determined; its enzymatic capacity and metabolite production were studied by HPLC; it was identified by the polymerase reaction technique (PCR); protein separation was performed by polyacrylamide gel electrophoresis (1D SDS-PAGE), and an enzyme search was performed. PCR analysis indicated that it corresponds to Microbacterium paraoxydans. It is a Gram-positive bacillus, with yellow pigmentation. It grew in a wide range of temperatures (15 to 37 °C), pH (5 to 9), and salt concentrations up to 5%, so can be considered as moderately halophilic. It fermented glucose, sucrose and mannitol;was positive for the enzyme lysine decarboxylase. The HPLC chromatogram showed two signals, corresponding to pyruvic acid and/or citric acid and a carotenoid. The 1D SDS-PAGE gel showed protein bands with molecular weights ranging from 20 to 250 kDa. These microorganisms produce diverse metabolites with potential for the development of new bioproducts or bioprocesses.
Keywords: biodiversity; enzymes; extremophiles; metabolites; microorganisms